Preparation and Characterization of Various Membrane Morphologies for Lateral Flow Immunoassay Development - Ahmad, A. L.; Low, S. C.; Abd Shukor, S. R.; Ismail, A. (Journal of Applied Membrane Science & Technology, 2017)
Lateral flow in nitrocellulose membrane is widely used as the transport medium in immunological test strips. The immunoassay performance depends greatly on the binding mechanism on membrane surface. If the membrane structures could be controlled precisely, various kinds of immunological analysis could be performed effectively and accurately. This study is aimed at a quantitative understanding on (1) the sensitivity of protein quantification on membrane surface by using densitometer and (2) comparison of the protein binding ability on different membrane surface pore structures. Concentration of immobilised protein on membrane surface was measured as a function of colour intensity, which is initially stained with Ponceau S. The findings showed that membrane morphologies significantly affect the sensitivity of membrane protein binding ability. Depending on the membrane pore structures, different red spot sharpness and intensities were observed from the stained protein dot. Membrane with smaller pore creates higher protein immobilization density and thus, increases the sensitivity level of the assay. However, larger membrane pore structure is necessary to induce rapid migration rate for faster assay.